Exploring factors influencing the selection of primary health care delivery models in conflict-affected settings of North West and South West regions of Cameroon and North-East Nigeria: A study protocol. - Lundi-Anne Omam; Kelli O'Laughlin; Nicholas Tendongfor; Zara Wudiri; Mohammed Ngubdo Hassan; Alain Metuge; Ooju Oluwafemi; Esther Omam; Rosalind Parkes-Ratanshi (PLoS ONE)
Background In conflict-affected settings, access to health care for displaced populations is constrained by barriers including geographical, cultural, communication, logistical, financial and insecurity. A six year humanitarian crises in the North West and South West regions of Cameroon has caused 27% of health facilities to be non-functional. The eleven year crisis in North-East Nigeria, has caused the closure of 26% of health facilities. These closure of health facilities and population displacement led to health care delivery using humanitarian funding by multiple different agencies. However, there is a paucity of evidence on the selection and design of the primary health care delivery models used in humanitarian settings. To ensure efficient use of resources and quality of services, model of care selection should be evidence based and informed by the specific humanitarian context. This research protocol aims to explore how primary health care models are selected by humanitarian organizations. Methods We will conduct a cross sectional quantitative survey to map the range of primary health care delivery models used by humanitarian organisations in Cameroon and Nigeria. Using in-depth interviews and focus group discussions with staff from humanitarian organizations and internally displaced persons, we will explore the factors influencing the selection of primary health care models in these settings and determine the coverage and gaps in services across the different primary health care models. Quantitative data will be analysed in a descriptive manner and qualitative data will be analysed thematically. Discussion Different models of care have been reported to be used by humanitarian organisations in conflict-affected settings, yet evidence on how different models are selected is lacking. A detailed understanding of the rationale for selection, the design and quality considerations of the strategies used to deliver health care will be obtained using a survey, in-depth interviews and focus group discussions.